1993
DOI: 10.1111/j.1470-6431.1993.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight status and weight dissatisfaction of college students enrolled in a basic nutrition course

Abstract: It has been suggested that general dissatisfaction with body weight, or anorexia‐like behaviour, may be higher in students majoring in home economics, specifically dietetics, than in students in non‐food and nutrition majors. This observation may be problematic in a student's future personal life or professional practice. The purpose of this study was to document the prevalence of general dissatisfaction with body weight, compared with actual body weight, in a group of college students enrolled in an introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Akan and Grilo3' image. 13,14,18,[32][33][34][35] found that Anglo-American women had more negative attitudes towards obesity, more body dissatisfaction and more disordered eating and dieting behaviours than did Asian or African-American women. Thompson et al 39 indicated that African-American male adolescents preferred a significantly heavier ideal female body size than white male adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Akan and Grilo3' image. 13,14,18,[32][33][34][35] found that Anglo-American women had more negative attitudes towards obesity, more body dissatisfaction and more disordered eating and dieting behaviours than did Asian or African-American women. Thompson et al 39 indicated that African-American male adolescents preferred a significantly heavier ideal female body size than white male adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…En este tenor, la variable insatisfacción corporal se manifestó significativamente en 33.51% de la muestra de alumnos, sin embargo este no fue el único factor detonante de la sintomatología dado que del mismo modo, los alumnos sin sintomatología la exhibían. Cabe hacer mención que los datos hallados para esta variable fueron menores en su distribución porcentual en comparación con lo mencionado en otras investigaciones en este grupo de estudiantes (44.23% a 83%; Rasor-Greenhaegh, Hurley, Witt, Brown & Rebovich, 1993;Rebello et al, 2004;Stipp & Oliveira, 2003).…”
Section: Discussionunclassified